(untitled) (American Journal of Islam and Society, 2015)
This seemingly modest volume is in fact the first comprehensive study of women in the Twelver Shi‘i scriptural sources. While studies on women abound, the vast majority are implicitly or explicitly grounded in the Sunni tradition; the infrequent Shi‘i expositions on women tend to be politicized, arcane, or even erroneous. In contrast, this groundbreaking work solidly introduces what the core Twelver Shi‘i sources say about women and integrates contemporary views. The sources of hadith and tafsīr used in this work represent mainstream historical currents of Shi‘i thought. For hadith, the author uses the Four Books, which were compiled in the tenth and eleventh centuries. While not considered infallible, they are treated as the most influential and reliable Shi‘i hadith collections and have had a formative impact on Shi‘i thought. Of course, this selection is not exhaustive; an even greater diversity of hadith appears in earlier as well as later compilations, especially the seventeenth-century encyclopaedic work Biḥār al-Anwār. In addition, the possibility exists that the Four Books’ treatment of women differs from that in other works. Therefore, this book should be seen as foundational and an invitation for further study, rather than as the final word on the subject. Note that this is not a criticism: Since many sections could easily be expanded into their own volume, it would not have been feasible to survey all extant Shi‘i hadith in a volume this size. Authors are, after all, only human. For tafsīr, the author uses Ali ibn Ibrahim al-Qummi’s Tafsīr al-Qummī (tenth century), al-Tusi’s Tibyān (eleventh century), al-Tabrisi’s Majma‘ al- Bayān (twelfth century), al-Huwayzi’s Nūr al-Thaqalayn (twelfth century), and Allamah Tabataba’i’s Tafsīr al-Mizān (twentieth century). This solid selection represents different time periods and approaches – the old and the new, the narrative and the analytical – but, again, is not absolutely comprehensive. In particular it omits mystical tafsīr, which might be expected to take a less earthly approach to gender. Additionally, the author gives her work a modern twist by considering ideas from contemporary writers on women in Islam who do not engage with the Shi‘i tradition, such as Amina Wadud, Fatima Mernissi, and Asma Barlas. She also frequently engages with the views of the Lebanese scholars Sayyid ...